What Makes Things Funny? An Integrative Review of the Antecedents of Laughter and Amusement. (February 2021) - Warren, Caleb; Barsky, Adam; McGraw, A. Peter
Despite the broad importance of humor, psychologists do not agree on the basic elements that cause people to experience laughter, amusement, and the perception that something is funny. There are more than 20 distinct psychological theories that propose appraisals that characterize humor appreciation. Most of these theories leverage a subset of five potential antecedents of humor appreciation: surprise, simultaneity, superiority, a violation appraisal, and conditions that facilitate a benign appraisal. We evaluate each antecedent against the existing empirical evidence and find that simultaneity, violation, and benign appraisals all help distinguish humorous from nonhumorous experiences, but surprise and superiority do not. Our review helps organize a disconnected literature, dispel popular but inaccurate ideas, offers a framework for future research, and helps answer three long-standing questions about humor: what conditions predict laughter and amusement, what are the adaptive benefits of humor, and why do different people think vastly different things are humorous?